Neurocognitive, physiological, and biophysical effects of transcranial alternating current stimulation. Issue 2 (February 2023) - Wischnewski, Miles; Alekseichuk, Ivan; Opitz, Alexander
Highlights: Transcranial alternating current stimulation (tACS) is a non-invasive method for brain stimulation. It is the application of alternating currents to the scalp that pass through head tissues and create an electric field in the brain, which modulates neural activity. The induced oscillatory electric fields can bias neural spike timing, synaptic plasticity, and long-range coherence. Neurophysiological effects can translate into changes in brain oscillatory power, frequency, and phase connectivity. Thereby, tACS can modulate cognitive and behavioral processes. tACS-induced brain modulation enables therapeutic applications in neurological and psychiatric conditions. Personalizing stimulation parameters such as intensity, waveform, and location can improve tACS efficacy. Further, advances in higher-dose interventions, multi-electrode network stimulation, and adaptive closed-loop applications show promise for future research. Abstract: Transcranial alternating current stimulation (tACS) can modulate human neural activity and behavior. Accordingly, tACS has vast potential for cognitive research and brain disorder therapies. The stimulation generates oscillating electric fields in the brain that can bias neural spike timing, causing changes in local neural oscillatory power and cross-frequency and cross-area coherence. tACS affects cognitive performance by modulating underlying single or nested brain rhythms, local or distal synchronization, and metabolic activity. Clinically, stimulation tailored to abnormal neural oscillations shows promising results in alleviating psychiatric and neurological symptoms. We summarize the findings of tACS mechanisms, its use for cognitive applications, and novel developments for personalized stimulation.